Neuroprotective effect of lithium on hippocampal volumes in bipolar disorder independent of long-term treatment response. Issue 3 (31st May 2013) - Hajek, T.; Bauer, M.; Simhandl, C.; Rybakowski, J.; O'Donovan, C.; Pfennig, A.; König, B.; Suwalska, A.; Yucel, K.; Uher, R.; Young, L. T.; MacQueen, G.; et al.
Abstract : Background: Neuroimaging studies have demonstrated an association between lithium (Li) treatment and brain structure in human subjects. A crucial unresolved question is whether this association reflects direct neurochemical effects of Li or indirect effects secondary to treatment or prevention of episodes of bipolar disorder (BD). Method: To address this knowledge gap, we compared manually traced hippocampal volumes in 37 BD patients with at least 2 years of Li treatment (Li group), 19 BD patients with <3 months of lifetime Li exposure over 2 years ago (non-Li group) and 50 healthy controls. All BD participants were followed prospectively and had at least 10 years of illness and a minimum of five episodes. We established illness course and long-term treatment response to Li using National Institute of Mental Health (NIMH) life charts. Results: The non-Li group had smaller hippocampal volumes than the controls or the Li group ( F 2, 102  = 4.97, p  = 0.009). However, the time spent in a mood episode on the current mood stabilizer was more than three times longer in the Li than in the non-Li group ( t 51  = 2.00, p  = 0.05). Even Li-treated patients with BD episodes while on Li had hippocampal volumes comparable to healthy controls and significantly larger than non-Li patients ( t 43  = 2.62, corrected p  = 0.02). Conclusions: Our findings support the neuroprotective effects of Li. The association between Li treatment and hippocampal volume seems to be independent of long-term treatment response and occurred even in subjects with episodes of BD while on Li. Consequently, these effects of Li on brain structure may generalize to patients with neuropsychiatric illnesses other than BD.